A holistic methodology for manufacturing systems configuration - Torayev, Agajan (2024)
The manufacturing sector is undergoing rapid transformations driven by global economic factors, technological advancements, and fluctuating market demands. These dynamics necessitate continuous innovation and adaptability in manufacturing systems to maintain competitiveness.